Proceedings of the 33rd Annual ACM/IEEE Symposium on Logic in Computer Science 2018
DOI: 10.1145/3209108.3209162
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo-quasi-polynomial algorithm for mean-payoff parity games

Abstract: In a mean-payoff parity game, one of the two players aims both to achieve a qualitative parity objective and to minimize a quantitative long-term average of payoffs (aka. mean payoff). The game is zero-sum and hence the aim of the other player is to either foil the parity objective or to maximize the mean payoff.Our main technical result is a pseudo-quasi-polynomial algorithm for solving meanpayoff parity games. All algorithms for the problem that have been developed for over a decade have a pseudo-polynomial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…This allows to simulate a parity game on an alternating Turing machine that uses poly-logarithmic space, which leads to a deterministic algorithm that uses quasipolynomial time and space. This new result has already inspired follow-up works [10,18,23,31,37]. However, benchmarks in the literature have demonstrated that both on random games and real examples the quasi-polynomial is not the best performing one.…”
Section: Introductionmentioning
confidence: 81%
“…This allows to simulate a parity game on an alternating Turing machine that uses poly-logarithmic space, which leads to a deterministic algorithm that uses quasipolynomial time and space. This new result has already inspired follow-up works [10,18,23,31,37]. However, benchmarks in the literature have demonstrated that both on random games and real examples the quasi-polynomial is not the best performing one.…”
Section: Introductionmentioning
confidence: 81%
“…In particular the last algorithm is of interest as an additional candidate for generalization to nested fixpoints, due to the known good performance of Zielonka's algorithm in practice. Daviaud et al [15] generalize quasipolynomial-time parity game solving by providing a pseudoquasipolynomial algorithm for mean-payoff parity games. On the other hand, Czerwinski et al [14] give a quasipolynomial lower bound on universal trees, implying a barrier for prospective polynomial-time parity game solving algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…In particular the last algorithm is of interest as an additional candidate for generalization to nested fixpoints, due to the known good performance of Zielonka's algorithm in practice. Daviaud et al [19] generalize quasipolynomial-time parity game solving by providing a pseudoquasipolynomial algorithm for mean-payoff parity games. On the other hand, Czerwinski et al [17] give a quasipolynomial lower bound on universal trees, implying a barrier for prospective polynomial-time parity game solving algorithms.…”
Section: Related Workmentioning
confidence: 99%